2016
DOI: 10.1111/jsap.12541
|View full text |Cite
|
Sign up to set email alerts
|

Use of CT to evaluate and compare intranasal features in brachycephalic and normocephalic dogs

Abstract: Nasal mucosal contact and caudal aberrant nasal turbinates were significantly more prevalent in brachycephalic dogs than in normocephalic dogs in our study. Computed tomography can be a valuable aid in obtaining data on nasal mucosal contact, caudal aberrant nasal turbinates and septal deviations. Combination of computed tomography with endoscopy and functional airway testing would be useful to further evaluate the correlation between intranasal features and symptoms of brachycephalic airway syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
20
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 28 publications
(63 reference statements)
4
20
0
3
Order By: Relevance
“…However, all pugs in this study had some degree of nasal septal deviation, whereas this finding was rare in bulldogs included here. One study found no difference in the prevalence of septal deviations between brachycephalic dogs and normocephalic dogs . In man, deviation of the nasal septum is a common cause of nasal obstruction but often remains asymptomatic.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, all pugs in this study had some degree of nasal septal deviation, whereas this finding was rare in bulldogs included here. One study found no difference in the prevalence of septal deviations between brachycephalic dogs and normocephalic dogs . In man, deviation of the nasal septum is a common cause of nasal obstruction but often remains asymptomatic.…”
Section: Discussionmentioning
confidence: 99%
“…These characteristics complement the description of lesions in BOAS and led to the development of surgical treatment options. These intranasal abnormalities are highly prevalent in brachycephalic dogs, and some of these lesions have been found in asymptomatic brachycephalic dogs as well as mesaticephalic dogs . The role of these intranasal abnormalities as indications for LATE remains unclear.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Imaging is used to support the diagnosis of brachycephalic obstructive airway syndrome by documenting obstructive tissue or areas of airway narrowing, and increasingly, advanced imaging such as computed tomography (CT) is often used as part of the diagnostic protocol. Computed tomography of the head and neck is used to document lesions such as a long and thickened soft palate , abnormally positioned turbinates (rostral or caudal aberrant turbinates), nasopharyngeal narrowing, laryngeal dimensions, and tracheal hypoplasia . The use of CT allows the thoracic cavity to be assessed and may reveal aspiration pneumonia secondary to regurgitation, bronchial collapse, esophageal thickening, or hiatal hernia.…”
Section: Introductionmentioning
confidence: 99%